Influence of interest in visual arts on the soft skills of future teachers - Aparicio-Flores, María Pilar; Esteve-Faubel, Rosa Pilar; Chust-Pérez, Verónica (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Art develops soft skills. However, the management of the latter and the work of the arts are relegated to the background in education. Hence, the need to observe the link between soft skills based on the low and high interest in visual arts in a sample of 589 future teachers. The results showed that interest in the visual arts was higher in most dimensions of soft skills. Likewise, these factors predict high interest in visual arts. Scientific knowledge in this field should be expanded.